The Role of Shame in Schizophrenia Delusion: The Interplay Between Cognitive-Perceptual and Emotional Traits. Issue 5 (May 2023) - Borrelli, Davide Fausto; Ottoni, Rebecca; Maffei, Simone; Marchesi, Carlo; Tonna, Matteo
Abstract: Through a strictly dimensional approach, the present study aimed at evaluating the interplay between cognitive-perceptual disturbances and emotional dispositions, particularly shame proneness, in schizophrenia delusion. One hundred one outpatients with schizophrenia were administered the Peters et al. Delusions Inventory, the Referential Thinking Scale (REF), the Magical Ideation Scale (MIS), the Perceptual Aberration Scale (PAS), the Positive and Negative Affect Schedule and the Experiences of Shame Scale (ESS). The severity of delusional ideation was positively related to all the cognitive-perceptual scales (REF, MIS, and PAS) and to shame proneness (ESS). Referential thinking (REF) emerged as the strongest predictor of delusion severity. The experience of shame played a mediation role in the relationship between cognitive-perceptual traits and delusional severity. These data suggest that severity delusion in schizophrenia depends, at least in part, on a complex interplay between cognitive-perceptual disturbances and experiences of shame.